Answer:
r = 0
Step-by-step explanation:
This is actually the first time I've actually had a equation with the variable equaling 0.
so first things first you have the equation:
r + 8 - 5r = 2(4 - 2r)
so you are going to add or multiply all the variable numbers together and the none variable numbers together like so:
r + (-5r) and (2*4) and (2* (-2r)) to get the equation looking like so:
8+ (-4r)= 8 -4r
you then add -4r to both sides to get this equation:
8+ ( -4r)= 8 -4r
+ 4r +4r
8 = 8 + r
you then subtract 8 from both sides to get r:
8 = 8 + r
-8 -8
0 = r
to check substitute the 0 into r in the equation:
r + 8 - 5r = 2(4 - 2r)
0 + 8 - (5*0) = 2(4- (2*0))
8 = 8
Tada!!!